Biodegradable Antimicrobial Agent/Analgesic/Bone Morphogenetic Protein-Loaded Nanofibrous Fixators for Bone Fracture Repair - Yu YH (Dove Medical Press, 2021)
Yi-Hsun Yu,1 Yu-Ting Lin,2 Yung-Heng Hsu,1 Ying-Chao Chou,1 Steve WN Ueng,1 Shih-Jung Liu1,2 1Department of Orthopedic Surgery, Bone and Joint Research Center, Chang Gung Memorial Hospital, Tao-Yuan, 33305, Taiwan; 2Department of Mechanical Engineering, Chang Gung University, Tao-Yuan, 33302, TaiwanCorrespondence: Shih-Jung LiuDepartment of Mechanical Engineering, Chang Gung University, 259, Wen-Hwa 1st Road, Kwei-Shan, Tao-Yuan, 333, TaiwanTel +886-3-2118166Fax +886-3-2118558Email shihjung@mail.cgu.edu.twPurpose: Postoperative infection and pain management are of great concern to orthopedic surgeons. Although there are several protocols available to deal with these aspects, they are fraught with complications, such as cartilage damage, cardiovascular and neurological intoxication, and systemic adverse responses. Therefore, it is necessary to develop safe and effective perioperative protocols. In the current study, antimicrobial agents/analgesics/growth factor-embedded biodegradable hybrid fixators (polycaprolactone fixator + poly[lactide-co-glycolide] sheath-core structured nanofibers) for bone fracture repair were designed.Methods: The biodegradable hybrid fixators were fabricated using solution-extrusion three-dimensional printing and electrospinning. In vitro, the characteristics of the hybrid fixators were examined. Additionally, the release of the incorporated vancomycin, ceftazidime, lidocaine, and bone morphogenetic protein-2 (BMP-2) was evaluated. The in vivo efficacy including drug-eluting properties, fracture repair, and pain management of the biomolecule-loaded nanofibrous fixators was investigated in rabbit rib-fracture models.Results: The nanofibrous fixators released vancomycin, ceftazidime, and lidocaine in a sustained manner under both in vitro and in vivo conditions and protected BMP-2 from burst release. The implantation of these hybrid fixators around the fractured rib significantly improved animal activities and bone union, indicating that the inclusion of analgesic in the fixator effectively reduced postsurgical pain and thereby helped in recovery.Conclusion: The novel biomolecule-loaded nanofibrous hybrid fixators resulted in excellent therapeutic outcomes. These fixators may be effective in the repair of rib fractures in clinical settings and may help mitigate surgical complications, such as infection, nonunion, and intolerable postoperative pain.Keywords: sheath-core structured nanofiber, bone union, biodegradable fixator, antimicrobial, analgesics, growth factor